Statistical Analysis of the Spanish National Football Team Matches at European CUP 2024 - Faiz Ardiyana; Ibnu Fatkhu Royana; Pandu Fatkhu Kresnapati (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. This research is innovative in that it seeks to provide information by analyzing each match between the Spanish team and various other countries. The analysis will encompass a variety of categories, such as play, shots, passes, ball possession, and shots on goal. The goal is to provide a comprehensive understanding of the supporting elements that can influence the outcome of a football match. Materials and Methods. This investigation employs a descriptive methodology, which is a research approach that is designed to provide a comprehensive account of existing phenomena, including those that are presently occurring and those that have occurred in the past. This study describes the condition of players in the Spanish team's Euro Cup match in the context of this study. The data is presented in the form of numerical data using audiovisual media aids, specifically recordings of the Spanish National Team's match in the 2024 Euro Cup in Germany, using a table format from Match Analysis. Result. The Spanish team has an average ball possession of over 50% and a ball possession of over 55%, with a total of over 500 passes in each match. Based on the number of shots toward the goal, the Spanish team has a higher average success rate than all other teams it has encountered, with an average of 52% and an average of 50% successful shots. Consequently, the Spanish team has a superior game control and a successful game. Conclusions. The Spanish Team will emerge as the champion of the 2024 Euro Cup by winning every match, beginning with the group stage, and continuing until they become the undisputed champions. This will be achieved by incorporating all the elements of a successful football game.